2018
DOI: 10.3390/min8110534
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of UAV and USV Data and Petrographic Analyses for the Investigation of Beachrock Formations: A Case Study from Syros Island, Aegean Sea, Greece

Abstract: Up until the last ten years, remote sensing data and especially high-resolution satellite data and airphotos were mainly used in shallow water mapping. The evolution and low cost of unmanned aerial vehicles (UAVs) provides a new tool for coastal area monitoring. This paper presents the synergistic use of a small commercial UAV and an unmanned surface vehicle (USV) for beachrock mapping in Syros Island, Greece. RGB images collected with a quadcopter were processed using Structure from Motion (SFM) photogrammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…UAV images were imported into the Agisoft PhotoScan software. The software combined computer vision techniques and structure from motion (SfM) photogrammetry to achieve direct georeferencing or bundle adjustment with ground control points (GCPs) [75,81,82] or simple similarity transformation over the whole block without GCPs. Alike to classic photogrammetry from air photos or satellite stereopairs, SfM photogrammetry uses overlapping images taken from different points of view.…”
Section: Uav Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…UAV images were imported into the Agisoft PhotoScan software. The software combined computer vision techniques and structure from motion (SfM) photogrammetry to achieve direct georeferencing or bundle adjustment with ground control points (GCPs) [75,81,82] or simple similarity transformation over the whole block without GCPs. Alike to classic photogrammetry from air photos or satellite stereopairs, SfM photogrammetry uses overlapping images taken from different points of view.…”
Section: Uav Data Processingmentioning
confidence: 99%
“…The geometry of the whole scene is built as more overlapping images are processed and more mutual objects are detected and related. The requirement for many overlapping photos in order to cover an entire area of interest generated the procedure name of structure from motion photogrammetry or photogrammetry produced from a moving camera [82].…”
Section: Uav Data Processingmentioning
confidence: 99%
“…Based on the analysis of the literature, two publications were found in which unmanned measurement platforms were used in hydrographic and photogrammetric surveys at the land-water interface zone [20,83]. In the article from 2018 [20] they were applied for the detection and Research has shown that, with the integration of hydrographic and photogrammetric data obtained using autonomous unmanned measurement platforms, it is possible to carry out terrain relief surveys at the land-water interface zone, meeting the requirements of the International Hydrographic Organization (IHO) Special Order [51]. It was also found that the main difficulty is to determine the depth between the coastline and the minimum depth recorded by the echo sounder (this area is devoid of real measurement data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are used for tasks related to supporting the navigation process [14], in underwater photogrammetry [15], or in geological works [16]. However, when it comes to unmanned aerial vehicles, they are used to: determine the terrain relief adjacent to the sea shore [17,18], monitoring coastline changes [19], in research on geomorphological processes occurring in the littoral zone [20,21], or in bathymetric surveys in shallow waters [22,23]. With these tools, it is possible to investigate complex hydrological processes occurring in the littoral zone [24][25][26], which result from a variety of natural phenomena and human intervention in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…USVs are characterized by small size, fast movement, and high flexibility. In recent years, they have been adopted to conduct missions such as marine rescue, environmental monitoring [2], island reef mapping [3], and resource exploration [4]. The safety of USVs is critical when conducting missions, and the roll motion is directly related to the safety and operating performance [5].…”
Section: Introductionmentioning
confidence: 99%